Al-Madrasah (Madrasah) am al-Madrasah al-’Āmmah (Sekolah): al-Mufaḍḍalah ‘inda Atbā’ Jam’iyyah al-Muḥammadiyyah wa Nahḍah al-’Ulamā fī Indūnīsiyā - Subhan, Arief (Studia Islamika, 2023)
This paper investigates the evolving landscape of Islamic education in Indonesia, focusing on the preferences of Muslim families affiliated with Muhammadiyah and NU towards madrasah and formal schools. Through a nuanced exploration of historical transformations, curriculum developments, and the socio-religious dynamics influencing educational choices, the study reveals a multifaceted interaction between religious identity, educational aspirations, and modernity. Utilizing unpublished 2010 survey data of PPIM UIN Jakarta, the research underscores a significant inclination towards integrating Islamic studies with general education, reflecting broader trends of Islamic education's modernization. This study not only enriches our understanding of Islamic pedagogy's role in shaping Indonesian society but also highlights the intricate interplay between religious affiliation and educational preferences in the world's largest Muslim-majority country.